Partial oxidation of methane to formaldehyde on chlorine-promoted catalysts - Baldwin, T; Burch, R; Squire, G; Tsang, S (1991)
The partial oxidation of methane to formaldehyde has been studied at atmospheric pressure and in the temperature range 450-650°C, under a variety of experimental conditions. Chlorine-modified supported palladium catalysts have been investigated, but in all cases the major product was carbon dioxide. Catalysts based on TiO2 have been tested in methane/air mixtures, both with and without the addition of small amounts of CH2Cl2. The addition of CH2Cl2 was found to significantly increase the conversion of methane in all cases. Formaldehyde selectivities in excess of 80% have been observed over an anatase phase at a conversion greater than 1%. The selectivity to formaldehyde was found to fall sharply with increasing methane conversion and this has been attributed to secondary oxidation of the formaldehyde. A yield of formaldehyde of 2.5% at 575°C has, nevertheless, been obtained over pure anatase. A heterogeneous-homogeneous mechanism is proposed in which methane is activated in the gas phase as a result of attack by radicals produced from the surface decomposition of CH2Cl2. This mechanism of secondary methane activation finds parallels in gas phase chemistry. It was further found that nitrous oxide was less effective than oxygen as an oxidant and this was attributed to the relative efficiency of the two oxidants in promoting the catalytic decomposition of CH2Cl2. © 1991.